(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the status of adherence to treatment for type 1 diabetes in patients at the central endocrine hospital in 2025. Methods: Cross-sectional study. Results: The treatment adherence rate among patients with type 1 diabetes at the National Hospital of Endocrinology in 2025 was high. Specifically, the good adherence rate to medication was 87.9%; the good adherence rate to blood glucose monitoring and regular check-ups was 94.9%; the adherence rate to dietary guidelines was 87.3%; and the adherence rate to physical activity was 96.2%. The average anxiety score among patients with type 1 diabetes was 1.84 ± 0.48 points. Conclusion: The good treatment adherence rate of patients with type 1 diabetes at the National Hospital of Endocrinology in 2025 was higher compared to specialized diabetes hospitals nationwide.